Numerical Study of Kaplan Propeller by Using CFD: Effect of Angle and Blade Diameter Variations - Mohammad Danil Arifin; Frengki Mohamad Felayati; Muswar Muslim; Ayom Buwono; Yeddid Yonatan Eka Darma (Institut Teknologi Sepuluh Nopember, 2023)
Efficient propeller performance contributes to better overall ship performance and speed. A well-designed propeller can optimize thrust generation, leading to improved maneuverability, responsiveness, and acceleration. It enables ships to maintain higher speeds while using less power, enhancing their competitiveness in the maritime industry. In this study, the Kaplan series propeller was analyzed by using Computational Fluid Dynamics (CFD). By modifying the angle of attack on the Kaplan propeller with 3, 4, and 5 blades, the distribution of the surface pressure, generated thrust, and torque value were easily identified and analyzed. The result shows that the change in the angle of attack influenced the pressure distribution on the back and face side of the propeller. The angle of attack is increased, and the pressure surface distribution also tends to increase. It has also affected the efficiency of the propeller performance which is expressed by the values of thrust propeller and torque. The more efficient the propeller performance, the less power it requires to produce the desired thrust.